The haunting [videorecording (DVD)] - Bont, Jan de; Neeson, Liam; Zeta-Jones, Catherine, 1969-; Wilson, Owen, 1968-; Jackson, Shirley, 1919-1965 ([publisher not identified], 2013)
Dr. Marrow lures three subjects to Hill House for a seemingly harmless experiment and together they discover its supernatural wrath.